1992
DOI: 10.1021/bi00141a027
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriorhodopsin can be refolded from two independently stable transmembrane helixes and the complementary five-helix fragment

Abstract: This paper describes experimental tests of the hypothesis that bacteriorhodopsin (BR) can fold by the association of independently stable transmembrane helices. Peptides containing the first and second helical segments of BR were chemically synthesized. These two peptides and the complementary five-helix fragment of BR were reconstituted in three separate populations of native-lipid vesicles which were then mixed and fused to allow the fragments to interact. After addition of retinal, absorption spectroscopy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 36 publications
3
91
0
2
Order By: Relevance
“…10 for review). The same kind of behavior has been documented in vitro by using fragments of proteins (14)(15)(16)(17). That fragments can reassociate and function argues that the covalent linkage between them, although perhaps adding stability and͞or control of expression, is not always essential.…”
Section: Methods and Resultsmentioning
confidence: 64%
“…10 for review). The same kind of behavior has been documented in vitro by using fragments of proteins (14)(15)(16)(17). That fragments can reassociate and function argues that the covalent linkage between them, although perhaps adding stability and͞or control of expression, is not always essential.…”
Section: Methods and Resultsmentioning
confidence: 64%
“…Transmembrane domains (TMs) are believed to be arranged in a barrel-like structure with a tightly packed core (2)(3)(4). Recent studies have suggested that GPCRs are composed of several independent folding units (5)(6)(7)(8)(9)(10)(11)(12)(13). Specifically, coexpression of polypeptides generated by splitting the muscarinic receptor in either the extracellular or the intracellular loops resulted in assembly of the molecules, which exhibited receptor-like function (6,7).…”
Section: G-protein-coupled Receptors (Gpcr)mentioning
confidence: 99%
“…First, the denatured apoprotein can be spontaneously refolded to the native state with quantitative recovery of secondary structure, chromophore binding, and proton-pumping activity (5,6). Reconstitution of the native structure has also been accomplished with complementary combinations of proteolytic fragments and synthetic peptides, comprising one or more of the transmembrane regions (7)(8)(9)(10)(11). Furthermore, refolding and chromophore binding has been demonstrated for numerous mutants containing amino acid substitutions, deletions, or insertions (12)(13)(14)(15).…”
Section: Bacteriorhodopsin (Br)mentioning
confidence: 99%